2022
DOI: 10.7150/thno.72786
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acylglycerol kinase sensitizes DLBCL to venetoclax via upregulation of FOXO1-mediated BCL-2 expression

et al.

Abstract: Background: Despite of the paradigm change on the treatments of acute myeloid leukemia (AML) and chronic lymphocytic leukemia (CLL) by venetoclax, it has been less successful in the treatment of diffuse large B-cell lymphoma (DLBCL). Here, we explored whether acylglycerol kinase regulates the sensitivity of DLBCLs to venetoclax and its mechanism in both cell lines and preclinical animal models. Methods: The expression of AGK and sensitivity to venetoclax of seven DLBCL cell lines were determined. Upon knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In contrast, the silence of SMIM26 decreased the level of mitochondrial AGK (Fig EV5A). Literature reported that AGK phosphorylated PTEN to restrict its function of activating AKT (Hu et al , 2019; Ning et al , 2022). Overexpression of AGK increased the mitochondrial and non‐mitochondrial AGK levels (Fig EV5B).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the silence of SMIM26 decreased the level of mitochondrial AGK (Fig EV5A). Literature reported that AGK phosphorylated PTEN to restrict its function of activating AKT (Hu et al , 2019; Ning et al , 2022). Overexpression of AGK increased the mitochondrial and non‐mitochondrial AGK levels (Fig EV5B).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, immune cells like CD8+ T cells must develop and maintain metabolic fitness in order to respond to unfavorable metabolic circumstances ( Figure 5 ). Acylglycerol kinase (AGK) positively regulates PTEN (phosphatase and tensin homolog) phosphorylation and inhibits PTEN’s phosphatase activity in CD8+ T cells when PTEN accumulates on the plasma membrane through the mediation of TCR and CD28, promoting activation of PI3K-mTOR modulating glycolysis, and controlling anti-tumor activity ( 82 ). In terms of functionality, AGK is essential for preserving CD8+ T cells’ metabolic fitness in the TME ( 83 ).…”
Section: Metabolic Fitnessmentioning
confidence: 99%
“…Forkhead box protein O1 (FoxO1), which is also known as forkhead rhabdomyosarcoma transcription factor, belongs to the forkhead box O (FoxO) transcription factor family and is in the center of the tumor molecular regulatory network 6,7 . Numerous studies have shown that the imbalance of FoxO1 is closely related to the pathological process of tumor development, invasion, and metastasis 7–11 . However, there is no unified conclusion about the effect of FoxO1 in OC.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Numerous studies have shown that the imbalance of FoxO1 is closely related to the pathological process of tumor development, invasion, and metastasis. 7 , 8 , 9 , 10 , 11 However, there is no unified conclusion about the effect of FoxO1 in OC. Some studies have shown that FoxO1 has a tumor suppressor role in OC.…”
Section: Introductionmentioning
confidence: 99%